2019
DOI: 10.1038/s41598-019-42247-1
|View full text |Cite
|
Sign up to set email alerts
|

Formation of tubules and helical ribbons by ceramide phosphoethanolamine-containing membranes

Abstract: Ceramide phosphoethanolamine (CPE), a major sphingolipid in invertebrates, is crucial for axonal ensheathment in Drosophila . Darkfield microscopy revealed that an equimolar mixture of bovine buttermilk CPE (milk CPE) and 1,2-dioleoyl- sn -glycero-3-phosphocholine (diC18:1 PC) tends to form tubules and helical ribbons, while pure milk CPE mainly exhibits amorphous aggregates and, at low frequency, straight needles. Negative staining electron microscopy indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…45 These structural parameters of GlcCer are also very similar to those reported for in vitro generated GalCer fibrils, where 20:1 Δ11 GalCer aggregates formed helical ribbons that have a right-handed twist with an average width of 30−35 nm and helical pitches of 80−90 nm. 46,47,64 Our combined FTIR and X-ray scattering results indicate that the free GlcCer spontaneously forms a lamellar phase in which the long-chain nonpolar tails of GlcCer monomers interact with each other to organize pairwise in a tail-to-tail configuration, and the polar glycan head groups remain exposed to the aqueous medium. The AFM analysis showed that the average width of the GlcCer fibrils was 29 ± 8 nm.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…45 These structural parameters of GlcCer are also very similar to those reported for in vitro generated GalCer fibrils, where 20:1 Δ11 GalCer aggregates formed helical ribbons that have a right-handed twist with an average width of 30−35 nm and helical pitches of 80−90 nm. 46,47,64 Our combined FTIR and X-ray scattering results indicate that the free GlcCer spontaneously forms a lamellar phase in which the long-chain nonpolar tails of GlcCer monomers interact with each other to organize pairwise in a tail-to-tail configuration, and the polar glycan head groups remain exposed to the aqueous medium. The AFM analysis showed that the average width of the GlcCer fibrils was 29 ± 8 nm.…”
Section: Discussionmentioning
confidence: 86%
“… 45 These structural parameters of GlcCer are also very similar to those reported for in vitro generated GalCer fibrils, where 20:1 Δ11 GalCer aggregates formed helical ribbons that have a right-handed twist with an average width of 30–35 nm and helical pitches of 80–90 nm. 46 , 47 , 64 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CPE has an essential role in axonal ensheathment and cortex glial plasma membrane expansion in Drosophila [15,63]. It was hypothesized that the axonal ensheathment in mammals and Drosophila is based on similar physical process with different lipids [62]. We have previously shown that sphingomyelin, a structural analog of CPE, could rescue cortex glial membrane defects in cpes mutants suggesting the head group is not as important as the tail in glial membranes.…”
Section: Discussionmentioning
confidence: 89%
“…Glycosphingolipids with VLC/ULC PUFAs have been shown to be required for mammalian male meiotic cytokinesis but their actual role has not been delineated [13, 60, 61]. It is interesting to note that CPE mimics certain physical properties of galactosylceramide (GalCer) a major sphingolipid in myelin sheath [62]. Previous studies have shown that CPE has an essential role in axonal ensheathment and cortex glial plasma membrane expansion in Drosophila [15, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CPE has an essential role in axonal ensheathment and cortex glial plasma membrane expansion in Drosophila [15,50]. It was hypothesized that the axonal ensheathment in mammals and Drosophila is based on similar physical process with different lipids [49]. We have previously shown that sphingomyelin, a structural analogue of CPE, could rescues cortex glial membrane defects in cpes mutants suggesting the head group is not as important as the tail group in glial membranes.…”
Section: Discussionmentioning
confidence: 89%